POSISI IDEAL PEREMPUAN KARIER DALAM RUMAH TANGGA PERSPEKTIF AL-QUR’AN - Nelli, Jumni; Afwan, Muhammad Muhsin (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The participation of women who have careers outside the household in order to support family finances has caused problems for women, because in the household, career women are still required to provide services like women who do not work. Even in some cases, career women are often blamed for the problems that arise in the family. The time taken to develop their careers and potential is seen as a source of conflict that shakes the unity of the family. Meanwhile, career women have different responsibilities than wives who do not work. In addition to having responsibilities in the household, the burden of work also depends on their shoulders to help the family's finances. This study aims to examine the ideal position of career women in the Qur'an, in order to educate husbands in treating working wives. The study was conducted by examining verses related to the position of women who have careers in the Qur'an. Searches for books of interpretation and the latest journals about the meaning of verses related to the research topic and then analyzed and obtained the substantive meaning of the verses. The results of this study indicate that there are no verses that prohibit women from having a career. The position of women with careers in carrying out their rights and obligations in the household is balanced. The Qur'an places a fair and equal position for women with men. Career women should be given more appreciation according to the burden they bear. A husband is expected to help his wife with housework, as an appreciation for his wife who has helped earn a living.